A new species of Lestrimelitta and a change in name in Lasioglossum (Hymenoptera: Apidae, Halictidae) - GONZALEZ, VICTOR H.; RASMUSSEN, CLAUS; VELASQUEZ, ALEXANDER (Revista Colombiana de Entomología, 2010)
A new species of cleptobiotic meliponine bee, Lestrimelitta piedemontana Gonzalez and Rasmussen sp. nov., is described based on workers captured in the Eastern Andes of Colombia. The geographical distribution of Lestrimelitta rufipes is also broadened, and the name Lasioglossum urbanus Gonzalez is changed to Lasioglossum santafensis Gonzalez and Rasmussen, nomen novum, in order to resolve the secondary homonymy with Lasioglossum urbanus (Smith, 1879).